2023
DOI: 10.3390/pr11061829
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating SARS-CoV-2 Vaccine Development: Leveraging Novel Hybrid Deep Learning Models and Bioinformatics Analysis for Epitope Selection and Classification

Abstract: It is essential to use highly antigenic epitope areas, since the development of peptide vaccines heavily relies on the precise design of epitope regions that can elicit a strong immune response. Choosing epitope regions experimentally for the production of the SARS-CoV-2 vaccine can be time-consuming, costly, and labor-intensive. Scientists have created in silico prediction techniques based on machine learning to find these regions, to cut down the number of candidate epitopes that might be tested in experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Due to their ability to facilitate the research and development of vaccines for a variety of illnesses that are rapidly developing, epitopes are essential for scientific and clinical investigations 23 . A potential vaccine against SARS-CoV-2 16 , 22 , 24 – 26 , malaria 27 , 28 , Ebola virus 29 , dengue virus field 30 , hepatitis B virus field 31 , Staphylococcus aureus 32 , 33 , Acinetobacter baumannii 34 36 , and Helicobacter pylori 37 has been developed using a variety of immuno-informatics techniques. Recently, numerous immunoinformatic tools such as 2 , 15 , 24 , 38 , 39 have been utilized in the design of TB epitope-based vaccines.…”
Section: Related Workmentioning
confidence: 99%
“…Due to their ability to facilitate the research and development of vaccines for a variety of illnesses that are rapidly developing, epitopes are essential for scientific and clinical investigations 23 . A potential vaccine against SARS-CoV-2 16 , 22 , 24 – 26 , malaria 27 , 28 , Ebola virus 29 , dengue virus field 30 , hepatitis B virus field 31 , Staphylococcus aureus 32 , 33 , Acinetobacter baumannii 34 36 , and Helicobacter pylori 37 has been developed using a variety of immuno-informatics techniques. Recently, numerous immunoinformatic tools such as 2 , 15 , 24 , 38 , 39 have been utilized in the design of TB epitope-based vaccines.…”
Section: Related Workmentioning
confidence: 99%
“…Traditional convolutional neural networks (CNNs) are usually used to process image data, and their basic structure is two-dimensional [40,41]. However, text can be regarded as one-dimensional sequence data, so the idea of a one-dimensional CNN can be borrowed and applied to text data to extract text features, which is the basic concept of TextCNN.…”
Section: Multi-scale One-dimensional Convolutional Neural Network Wit...mentioning
confidence: 99%
“…DL efficiently reduces time, expense, and burden on COVID-19 diagnosis 32 34 . For instance, Yang et al 35 , Ameen et al 36 , Abbasi et al 37 suggested computational and deep learning approaches to create multi-epitope-based vaccines against SARS-CoV-2. They found several potential peptide vaccines that may be further tested utilising experimental studies, in addition to showing that their technique creates vaccine candidates with useful immunogenicity and minimal toxicity.…”
Section: Introductionmentioning
confidence: 99%